Engaging with Tapa and Ngatu: Creating Space for Storying About Tongan Identity and Culture in Aotearoa New Zealand - Fonua, Fire U. F. A. T. M. I.; Fonua, Sonia M.; Fonua, Lavinia T.; Burrows, Sulieti Fieme’a; Gillies, Tui Emma (Art/Research International)

(untitled) (University of Alberta, 2024)
The making and gifting of koloa faka-Tonga (women’s valuables, also known as koloa) has been an integral part of Tongan identity and culture for as long as anyone can remember. Working collaboratively on tapa and ngatu provides space for discussions and understanding, and reflections of Tongan identity and culture. The practice of gifting koloa has continued outside of the Kingdom of Tonga as Tongans migrate for new opportunities, including Aotearoa New Zealand (henceforth Aotearoa NZ). Using two different examples, this article will explore, through talatalanoa, how Tongan family partnerships working with tapa/ngatu in contemporary ways are sites of intergenerational knowledge sharing through art practices in Aotearoa NZ. Sulieti Burrows and Tui Emma Gillies are a mother-daughter partnership of tapa artists who work and reside in Aotearoa NZ and use their time together to share stories and make tapa works depicting what concerns them in contemporary society. Also residing in Aotearoa NZ, Lavinia and Fire Fonua are a mother-son partnership who turn koloa into contemporary personal adornment, alongside Fire’s wife, Sonia. In this article, the four Tongan authors’ reflections on inter-generational knowledge sharing and practices related to koloa making and gifting are described and illustrated using examples of their work. Their diverse stories also reflect on Tongan material culture, and Tongan identity, and demonstrate how working on practices that centre koloa provides opportunities to consider what it means to be Tongan in Aotearoa NZ, and how Tongan ways of being, knowing, and doing are valued as tu’atonga.